Simplified Evaluation of Ground Motion Amplification in the Vicinity of a Topographic Feature. Issue 13 (3rd October 2022) - Sierra, César; Jaramillo, Juan; Gomez, Juan; Sáenz, Mario; Vergara, Juan
ABSTRACT: A two-parameter expression for the quantification of topographic effects in ground response analysis at sites located in the vicinity of a topographic feature is presented. The expression is derived from parametric analysis of convex and concave canonical shapes after identifying that the diffracted field in these geometries remains relatively stable in the low dimensionless frequency regime. The proposed expression is used in the estimation of topographic effects at two sites located in realistic topographic scenarios over a given period range. To show the quality of the approximate formula results are compared with numerical simulation values.